COMPARATIVE ANALYSIS OF WATER CONTENT AND INORGANIC SALT LEVELS IN FEMALE ATHLETES AND NON-ATHLETE FEMALES: IMPLICATIONS FOR HYDRATION AND ELECTROLYTE BALANCE - Naseer Ud Din Waza; Naseer Mushtaq Rather (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Background: Maintaining hydration and balancing electrolytes are crucial for essential physiological functions, including muscle contraction, thermoregulation, and cellular activity. It is well established that physical activity influences body composition, encompassing total body water and mineral content. However, there has been little research that specifically compares hydration-related parameters such as water content and levels of inorganic salts between physically active and inactive female populations. Understanding these alterations can shed light on the physiological advantages of regular physical activity for females. Objective: The objective of this study was to compare and analyze the water content and inorganic salt between female athletes and non-athletes. Materials and Methods: A Total of 30 females N=30 were selected, using a convenience sampling technique. The participants were between 20-25 years old. To achieve the purpose of the study masters of physical education students (n=15) from Department of physical education Punjabi University Patiala, Punjab were selected, and the non-athlete female students of pharmacy department and computer science department (n=15) from Punjabi University Patiala Punjab were selected. To achieve the purpose of the study, Body composition analyser GS6.5B Body Building Weight Test System (Version 1.0) was used to measure the water content percentage and inorganic salt percentage of the subjects. Results: The female athletes exhibited a significantly higher percentage of water content compared to non-athlete females, t-value= 6.81, p=0.0001, indicating a statistically significant difference (p < 0.05) and the percentage of inorganic salt content was also significantly higher in female athletes compared to non-athlete, t-value= 2.43, p=0.02, indicating a statistically significant difference (p < 0.05). Conclusion: The present study concludes that female athletes possess significantly higher percentages of total body water and inorganic salt content compared to non-athlete females.